2019
DOI: 10.1088/1674-1056/28/7/077404
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the f–c hybridization in the ordered uranium films on W(110)*

Abstract: A key issue in metallic uranium and its related actinide compounds is the character of the f electrons, whether it is localized or itinerant. Here we grew well ordered uranium films on a W(110) substrate. The surface topography was investigated by scanning tunneling microscopy. The Fermi surface and band structure of the grown films were studied by angle-resolved photoemission spectroscopy. Large spectral weight can be observed around the Fermi level, which mainly comes from the f states. Additionally, we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Similar behavior could be found in the other CDW materials [5,33,34]. From the angleresolved photoemission spectroscopy of uranium films on W(110), large spectral weight was observed around the Fermi level [32].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar behavior could be found in the other CDW materials [5,33,34]. From the angleresolved photoemission spectroscopy of uranium films on W(110), large spectral weight was observed around the Fermi level [32].…”
Section: Introductionsupporting
confidence: 79%
“…In bulk single crystal, strain can be applied by attaching materials to piezoelectric substrates. While in thin films, strain For uranium, the epitaxial thin film, in which the strain is present, has already led to the discovery of a wide range of new structural, magnetic, and electronic phenomena [21,[28][29][30][31][32]. The hcp phase of uranium, which does no exist in the bulk, could be stabilized on Gd/Nb substrate [31].…”
Section: Introductionmentioning
confidence: 99%
“…STM/STS results showed that the U density of states close to the Fermi level is dominated by the 5f states [129]. STS and ARPES showed both the Fermi surface topology and electronic structure of ordered α-U films [134]. ARPES studies of epitaxial thin films of the oxides PuO 2 and NpO 2 [20,135], and uranium carbide (UC 2 ), reveal the importance of the underlying substrate structure in stabilizing the epitaxial film [136].…”
Section: B Characterization Of Thin Filmsmentioning
confidence: 99%
“…The impedance of an electrolyte depends on its temperature and measurement frequency . Therefore, a stable and tightly controlled temperature is very important for impedimetric measurements where the sensor needs to detect a change in impedance caused by the presence of its bio‐molecular targets.…”
Section: Materials and Fabricationmentioning
confidence: 99%